Adipolin/CTRP12 protects against pathological vascular remodelling through suppression of smooth muscle cell growth and macrophage inflammatory response. Issue 1 (15th March 2019) - Ogawa, Hayato; Ohashi, Koji; Ito, Masanori; Shibata, Rei; Kanemura, Noriyoshi; Yuasa, Daisuke; Kambara, Takahiro; Matsuo, Kazuhiro; Hayakawa, Satoko; Hiramatsu-Ito, Mizuho; Otaka, Naoya; Kawanishi, Hiroshi; et al.
Abstract: Aims: Secreted factors produced by adipose tissue are involved in the pathogenesis of cardiovascular disease. We previously identified adipolin, also known as C1q/TNF-related protein 12, as an insulin-sensitizing adipokine. However, the role of adipolin in vascular disease remains unknown. Here, we investigated whether adipolin modulates pathological vascular remodelling. Methods and results: Adipolin-knockout (APL-KO) and wild-type (WT) mice were subjected to wire-induced injury of the femoral artery. APL-KO mice showed increased neointimal thickening after vascular injury compared with WT mice, which was accompanied by an enhanced inflammatory response and vascular cell proliferation in injured arteries. Adipolin deficiency also led to a reduction in transforming growth factor-β (TGF-β) 1 protein levels in injured arteries. Treatment of cultured macrophages with adipolin protein led to a reduction in lipopolysaccharide-stimulated expression of inflammatory mediators, including tumour necrosis factor (TNF)-α, interleukin (IL) 6, and monocyte chemotactic protein (MCP)-1. These effects were reversed by inhibition of TGF-β receptor II (TGF-βRII)/Smad2 signalling. Adipolin also reduced platelet-derived growth factor (PDGF)-BB-stimulated proliferation of vascular smooth muscle cells (VSMCs) through a TGF-βRII/Smad2-dependent pathway. Furthermore, adipolin treatment significantly increased TGF-β1 concentration in media from cultured VSMCs and macrophages. Conclusion: These data indicate that adipolin protects against the development of pathological vascular remodelling by attenuating macrophage inflammatory responses and VSMC proliferation.